Estimation of the Treatment Effects of Ownership on the Indirect Financing of Small- and Medium-Sized Enterprises - Xiuzhen Wang; Yi Hu; Xiaohua Xia; Ying Deng (Discrete Dynamics in Nature and Society)
Small- and medium-sized enterprises (SMEs) are the important driving forces for the growth of China’s economy. However, financing difficulty has always been the important problem besetting the development of SMEs for a long time. In particular, in recent years, US subprime crisis in 2008 caused a heavy blow to the development of some externally oriented SMEs. Thus, how to effectively overcome financing predicament for the SMEs is crucial for Chinese government. In this paper, based on microdata from China Industrial Enterprise Database, propensity score matching (PSM) method is adopted to conduct empirical analysis about the treatment effects of indirect financing level of SMEs under different systems. Empirical results reveal that state-owned enterprises enjoy indirect financing advantages compared with other enterprises and there is certain ownership discrimination against foreign-funded enterprises and private enterprises. In particular, the indirect financing rate of state-owned enterprises is 1.4% higher than that of other enterprises, and the indirect financing rate of foreign-funded enterprises is 6% lower than that of other enterprises; private enterprises are advantageous in indirect financing compared with other enterprises; however, indirect financing rate of private enterprises is 1.8% lower than that of state-owned enterprises, which also reveals ownership discrimination to certain extent.